The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/1933719114542019
|View full text |Cite
|
Sign up to set email alerts
|

Ulipristal Acetate Modulates the Expression and Functions of Activin A in Leiomyoma Cells

Abstract: Uterine leiomyoma is the most common benign gynecological tumor in women of reproductive age and represents the single most common indication for hysterectomy. A development of new treatments is necessary for a medical management, and in this direction, several hormonal drugs are under investigation. Ulipristal acetate (UPA; a selective progesterone receptor modulator) is considered as one of the most promising because progesterone has a critical role in development and growth of uterine leiomyoma. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…An in vitro study demonstrated another possible mechanism of action of UPA: inhibition of activin A expression and function in cultured leiomyoma cells ( Ciarmela et al ., 2014 ).…”
Section: The Future Of Medical Therapymentioning
confidence: 99%
“…An in vitro study demonstrated another possible mechanism of action of UPA: inhibition of activin A expression and function in cultured leiomyoma cells ( Ciarmela et al ., 2014 ).…”
Section: The Future Of Medical Therapymentioning
confidence: 99%
“…It also decreases activin binding proteins, follistatin, activin receptor type (ActRIIB), and activin receptor-like kinase 4 (Alk4) mRNA expressions. In addition, it was able to block the activin A-induced increase in fibronectin or VEGF-A mRNA expression [ 101 ]. Moreover, ECM deposition in UF is also reduced by UPA due to increasing both matrix metalloproteinases (MMPs) and ECM metalloproteinase inducer (EMMPRIN) while reducing tissue inhibitor of metalloproteinases (TIMPs) [ 100 , 102 ].…”
Section: Treatment Options For Uterine Fibroidsmentioning
confidence: 99%
“…Moreover, ECM deposition in UF is also reduced by UPA due to increasing both matrix metalloproteinases (MMPs) and ECM metalloproteinase inducer (EMMPRIN) while reducing tissue inhibitor of metalloproteinases (TIMPs) [ 100 , 102 ]. Finally, UPA also increases the ratio of progesterone receptor isoforms (PR-A/PR-B) as it decreases PR-B receptor expression while increases PR-A so UPA inhibits progesterone-mediated effects on fibroid cells [ 98 101 , 103 108 ]. Figure 4 summarizes UPA mechanisms of action presented in the literature so far.…”
Section: Treatment Options For Uterine Fibroidsmentioning
confidence: 99%
“…2012 ). Ulipristal was shown to block the expression of fibronectin and VEGFA mRNA induced by activin A in cultured leiomyoma cells, thus blocking cell growth ( Ciarmela et al . 2014 ) and the substantial angiogenesis required by these tumors to proliferate ( Xu et al .…”
Section: Mechanisms Of Growth Inhibition Driven By Antiprogestinsmentioning
confidence: 99%